Infusing Local Tradition Values into School Culture: How Indonesian Islamic School Set Up Character Education? - Mulyadin, M; Jaedun, Amat (LP2M - Universitas Islam Negeri (UIN) Walisongo, 2018)
The purpose of this study is to reveal the internalization of the maja labo dahu values in character education. The method used is a case study with a qualitative approach. The determination of the research subject is carried out by purposive technique consisting of students and people in MTs Negeri 1 Bima. The sources of data are oral sources, artifacts, documents, and written records. Data are collected through observation, interviews, and documentation. Data validity test is carried out by using triangulation. Data are analyzed by using qualitative analysis techniques of interaction model with steps of data collection, data reduction, data presentation, and conclusions. The results showed that the values of the maja labo dahu are in accordance with the values in character education, namely religious values, honesty, discipline, independence, patriotism, and environmental awareness. Besides, these values have effectively provided moral knowledge to students. The constraints experienced by schools in internalizing these values in character education are the lack of consistency of students parents or the surrounding environment in supporting and developing the cultural values of the maja labo dahu.